Regioselective synthesis of new 2-(E)-cyano(oxazolidin-2-ylidene)thiazoles - Bakavoli, Mehdi; Beyzaei, Hamid; Rahimizadeh, Mohammad; Eshghi, Hossein (European Journal of Chemistry, 2011)
Reaction of 2-(oxazolidin-2-ylidene)malononitrile (1) with phosphorus pentasulfide gave the corresponding thioamide derivative (2a) in a regioselective manner. Reaction of this compound with several α-bromocarbonyl compounds gave new 2-(E)-cyano(oxazolidin-2-ylidene)thiazoles (3a-g). The chemical structures of novel compounds were confirmed by 1H NMR, elemental analysis, FT-IR spectrometry and mass spectrophotometric analyses.